THU0409 Optimizing Fracture Prevention: The Fracture Liaison Service, an Observational Study. (23rd January 2014) - Eekman, D.; van Helden, S.; Huisman, M.; Verhaar, H.; Bultink, I.; Geusens, P.; Lips, P.; Lems, W.
Abstract : Background: In about 5% of elderly fracture patients the presence or absence of underlying osteoporosis was investigated before the introduction of fracture liaison services. Objectives: Increase the percentage of elderly fracture patients undergoing a dual energy x-ray absorptiometry (DXA) measurement, and investigate why some patients did not respond to invitation to our fracture liaison service (FLS). Methods: In four Dutch hospitals fracture patients ≥ 50 years were invited for a DXA measurement and visit to our FLS. Patients who did not respond, were contacted by telephone. In patients diagnosed with osteoporosis, treatment was started. Patients were contacted every three months during one year to assess drug persistence and the occurrence of subsequent fractures. Results: Of the 2207 patients that were invited: 50, 6% responded. Most frequent reasons for not responding included: not interested (38%), already screened/under treatment for osteoporosis (15.7%), physically unable to attend the clinic (11.5%) and death (5.2%). Hip fracture patients responded less frequently (29%) while patients with a wrist (60%), or ankle fracture (65.2%) were more likely to visit the clinic. In 337 responding patients osteoporosis was diagnosed and treatment was initiated. After 12 months of follow-up, 88% of the patients were still persistent with anti-osteoporosis therapy and only 2% suffered a subsequent clinical fracture. Conclusions: In elderly fracture patients, the use of a FLS leads to an increased response rate, a high persistence to drug treatment, and a low rate of subsequent clinical fractures. Additional programs for hip fracture patients are required, as these patients have a low response rate. Acknowledgements: Dineke Timmer, Greetje Asma, Elaine Menasse, Gittie Willems, Kirsten Huntjens, Monique Samson, Jantine van Driel, Alice van Iersel, Yvette van Houdt, Anneke van Baarsel Disclosure of Interest: None Declared